Yield and nutrition of greenhouse-grown strawberries (Fragaria × ananassa (Duchesne ex Weston) Duchesne ex Rozier. cv. Camarosa) as affected by potassium fertilization (2018)
In strawberry, potassium fertilization has been little studied, which difficult management strategies for an increasing yield and understanding the use of this nutrient in strawberry crop. The aim of this study was to evaluate the influence of sources and rates of potassium (K) fertilizers on yield, K level and agronomic traits of strawberry cv. Camarosa fruit, carried out under greenhouse conditions. A randomized in a completely block design with four replicates in a factorial arranged 6x3 (six rates of potassium x three sources of potassium fertilizers), was performed. Fertilizers sources used were as follows: potassium sulphate, potassium nitrate and potassium chloride in 0, 60, 120, 180, 240 and 300 kg ha-1 K2O doses. An increasing potassium rates have allowed a higher potassium content in leaves and fruits. A higher potassium content in leaves was obtained by KNO3 (11.70 g kg-1). Yield, fruit number per plant and potassium extraction per plant, increased linearly with the evaluated doses and fruit average weight at a dose of 183 kg ha-1. There was no significant difference among potassium content in leaves. Strawberry production is maximized through potassium fertilization, independent of the source origin.